Worry about performance: a unique dimension of caregiver burden. (April 2014) - Lim, Wee Shiong; Cheah, Wee Kooi; Ali, Noorhazlina; Han, Huey Charn; Anthony, Philomena Vasantha; Chan, Mark; Chong, Mei Sian
ABSTRACT Background: Recent studies that describe the multidimensionality of the Zarit Burden Interview (ZBI) challenge the traditional dual-factor paradigm of personal and role strains (Whitlatch et al., 1991). These studies consistently reported a distinct dimension of worry about caregiver performance (WaP) comprising items 20 and 21.The present study aims to compare WaP against conventional ZBI domains in a predominantly Chinese multi-ethnic Asian population. Methods: We studied 130 consecutive dyads of family caregivers and patients. Factor analysis of the 22-item ZBI revealed four factors of burden. We compared WaP (factor 4) with the other three factors, personal strain, and role strain via: internal consistency; inter-factor correlation; item-to-total ratio across Clinical Dementia Rating (CDR) stages; predictors of burden; and interaction effect on total ZBI score using two-way analysis of variance. Results: WaP correlated poorly with the other factors (r = 0.05–0.21). It had the highest internal consistency (Cronbach's α = 0.92) among the factors. Unlike other factors, WaP was highly endorsed in mild cognitive impairment and did not increase linearly with disease severity, peaking at CDR 1. Multiple regression revealed younger caregiver age as the major predictor of WaP, compared with behavioral and functional problems for other factors. There was a significant interaction between WaP and psychological strain (p = 0.025). Conclusion: Our results corroborate earlier studies that WaP is a distinct burden dimension not correspondent with traditional ZBI domains. WaP is germane to many Asian societies where obligation values to care for family members are strongly influential. Further studies are needed to better delineate the construct of WaP.